Literature Review: Factors Affecting Productivity in Mining Industries - Mochammad Mukti Ali; Aidil Arifin; Aris Setiyani (Dinasti Publisher, 2025)
Mining remains an indispensable pillar of the global economy, supplying essential resources for construction, manufacturing, and the ongoing energy transition. Yet across the last decade, productivity growth in mining industries has been inconsistent despite enormous technological advances and increased investment in mechanisation and digitalisation. This literature review synthesises over 50 peer-reviewed studies and industry reports published between 2015 and 2025 to identify and evaluate the main factors influencing productivity in global mining operations. The analysis groups findings into seven thematic categories: (1) human capital and organisational culture, (2) equipment utilisation and maintenance practices, (3) technological adoption and automation, (4) geological and environmental constraints, (5) supply-chain and logistics efficiency, (6) regulatory and sustainability pressures, and (7) macroeconomic and cyclical influences. Recent evidence shows that the productivity gap between high-performing and average mines is widening, driven not by resource quality alone but by differences in managerial capability, data utilisation, and operational integration. Emerging literature emphasises that productivity enhancement requires a holistic, system-based approach that combines technological innovation with workforce competence, sustainability alignment, and governance reform. The review concludes that the next decade will demand a re-conceptualization of productivity from narrow cost-per-tonne metrics toward integrated measures of digital efficiency, environmental resilience, and social value creation.